The Role Of Emotional Intelligence In Mediating The Effect Of Workload And Organizational Commitment On Turnover Intention - Fauzan Rochim; Pahlawansjah Harahap; Albert Albert (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the effect of workload and organizational commitment on turnover intention with emotional intelligence as a mediating variable among employees in the manufacturing sector. A quantitative approach with a survey method was employed, using proportionate stratified random sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS, including validity, reliability, goodness-of-fit, and mediation testing through bootstrapping. The results indicate that workload has a positive effect on turnover intention, while organizational commitment has a negative effect. Emotional intelligence does not significantly influence turnover intention and does not mediate the relationship between workload and organizational commitment on turnover intention. These findings suggest that organizational factors play a more dominant role than individual factors in explaining turnover intention, particularly in manufacturing industries characterized by high operational demands.